Pregnant and Parenting Women's Experiences with Substance Use Disorder. Issue 5 (September 2021) - Wright, Mary Ellen; Temples, Heide S.; Shores, Emily; Chafe, Olivia; Lannamann, Rebekkah; Lautenschlager, Carla
Abstract: Purpose: The purpose of the study was to describe and analyze the experience of women with substance use disorder during pregnancy and parenting to inform health care services that promote recovery. Study Design: Interviews of pregnant or parenting women with substance use disorder were used in this qualitative descriptive study. Methods: Participants were recruited from two recovery centers serving pregnant or parenting women with substance use disorder. Participants called a study cellphone to speak with the researchers about their substance use and recovery. Four independent reviewers conducted thematic analysis and were facilitated by Atlas.ti qualitative analysis program. Results: N = 15 women called the study cellphone; 10 met inclusion criteria and were interviewed. Researchers coded 81 themes with the common occurrence of prior trauma, multiple substances used, stigma and judgment from others, and having children as a motivation to seeking recovery. Co-occurrence of themes of positive social support and the pursuit of recovery was identified. Clinical Implications: Positive social support co-occurring with recovery supports the need for strengthened social support structures. Health care professionals should intentionally address the culture of caring for pregnant and parenting women with substance use disorder through education, practice, advocacy, and research. Abstract : Ten pregnant women and new mothers shared their experiences with substance use disorder via interviews in this qualitative study. Common themes include occurrence of prior trauma, multiple substances used, stigma and judgement from others, and having children as a motivation to seeking recovery. Suggestions for supportive care for women with substance use disorder are offered based on participants' experiences.